2006
DOI: 10.1074/jbc.m509409200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Inclusions Containing Mutant α1-Antitrypsin Z Are Propagated in the Absence of Autophagic Activity

Abstract: Mutant ␣ 1 -antitrypsin Z (␣ 1 -ATZ) protein, which has a tendency to form aggregated polymers as it accumulates within the endoplasmic reticulum of the liver cells, is associated with the development of chronic liver injury and hepatocellular carcinoma in hereditary ␣ 1 -antitrypsin (␣ 1 -AT) deficiency. Previous studies have suggested that efficient intracellular degradation of ␣ 1 -ATZ is correlated with protection from liver disease in ␣ 1 -AT deficiency and that the ubiquitin-proteasome system accounts fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
263
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(275 citation statements)
references
References 41 publications
11
263
0
1
Order By: Relevance
“…28 The results demonstrated a significant delay in disposal of ATZ in the atg5-null background compared with the wild-type background. There was progressive accumulation of insoluble ATZ with very large inclusions extending from the ER into the cytoplasm in many of the atg5-null cells.…”
Section: Genetic Evidence For Autophagic Disposal Of Mutant Atzmentioning
confidence: 86%
“…28 The results demonstrated a significant delay in disposal of ATZ in the atg5-null background compared with the wild-type background. There was progressive accumulation of insoluble ATZ with very large inclusions extending from the ER into the cytoplasm in many of the atg5-null cells.…”
Section: Genetic Evidence For Autophagic Disposal Of Mutant Atzmentioning
confidence: 86%
“…To prevent the toxicity, cell degrades accumulated ATZ by ERAD. Recently, proteins involved in autophagy were shown to participate in the removal of ATZ aggregates, indicating that autophagy also is utilized to degrade this protein; [8][9][10] however, the relationship between autophagy and ER stress had not been clear. We recently found that autophagy is indeed induced in response to ER stress.…”
Section: Introductionmentioning
confidence: 99%
“…58 In cells overexpressing ATZ, autophagosomes seem to be closely juxtaposed with the ATZ aggregates, and suppressing autophagy retards the removal of ATZ. 59 Furthermore, in the yeast model of ATZ degradation, it has also been found that aggregated ATZ is targeted to the autophagy pathway for degradation. 60 It is thus conceivable that autophagy can play an important role in the liver pathogenesis of AT deficiency.…”
Section: Role Of Autophagy In Clearing Misfolded Proteins In Liver DImentioning
confidence: 99%